1989
DOI: 10.1364/josaa.6.000153
|View full text |Cite
|
Sign up to set email alerts
|

Hue signals from short- and middle-wavelength-sensitive cones

Abstract: Hue sensations resulting from the selective stimulation of short-wavelength-sensitive (S) and middle-wavelength-sensitive (M) cones were deduced from measurements of spectral unique green and unique blue under conditions of high or low S-cone sensitivity relative to M- and long-wavelength-sensitive-cone sensitivity. Selective reduction of S-cone stimulation shifted unique blue toward shorter wavelengths and unique green toward longer wavelengths, implying losses of perceived yellowness and short-wavelength red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 13 publications
5
18
0
Order By: Relevance
“…Nonetheless, several of these earlier studies (19)(20)(21)(22) reported that small short-wavelength spots were seen as blue-green, in accord with our data.…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, several of these earlier studies (19)(20)(21)(22) reported that small short-wavelength spots were seen as blue-green, in accord with our data.…”
Section: Discussionsupporting
confidence: 92%
“…If correct, then human perceptions should be predictable from the responses of those cells; however, there are conspicuous differences between human color vision and what is predicted from the responses of S-(LþM) and L versus M cells (DeValois and DeValois 1993). The contradiction between human perception and L versus M midget ganglion cell responses arises because S cones have an input to perceptual redness and greenness but they do not have an input to the putative canonical (L-M) "red-ON" and (M-L) "green-ON" midget ganglion cells of the standard model (Drum 1989;DeValois and DeValois 1993;Dacey 2000). Excitatory S-cone input contributes to the perception of both blue and red and inhibitory S-cone input contributes to the perceptions of both yellow and green.…”
Section: Recent Evidence Points To a New Hypothesis For The Biologicamentioning
confidence: 99%
“…Mid-spectral tests can also appear blue when flashed on achromatic fields. [5][6][7] The subject of Ingling, Scheibner, and Boynton 8 identified one-fifth of the mid-spectral incremental flashes as blue, when these were presented at 32ϫ threshold on 1000 td blue and green fields. Such flashes may have excited other classes of cones as well as M-cones, but DeValois, DeValois, Switkes, and Mahon 9 report that 2°test flashes isolated to M-cones typically appear slightly bluish-green when presented on a white field.…”
Section: Appearance Of Mid-spectral Stimulimentioning
confidence: 99%
“…In more recent models, however, M-cones do contribute to blue. 6,7 For example, in the multistage model of DeValois and DeValois, 12 M-cones can contribute 3 times more than S-cones to blue. We were concerned in the present research with the color-naming of M-cone isolated stimuli presented briefly on a range of colored adaptation fields, not limited to black or white.…”
Section: Appearance Of Mid-spectral Stimulimentioning
confidence: 99%